The Urgency to Use the Rabat Plan of Action in the Hate Speech Offense - Mahdi, Octavia Rahma; Rinwigati, Patricia (Universitas Airlangga, 2024)
The broad spectrum of hate speech makes it difficult for law enforcement officials to identify which speech can be punished. This difficulty creates uncertainty in law enforcement and potentially triggers injustice. Therefore, this article emphasizes the importance of assessing the multidimensional aspects accommodated in the Rabat Plan Action instrument to determine hate speech. The Rabat Plan of Action instrument is one of the international human rights instruments drafted to handle acts of hate speech without regard to the right to freedom of expression. The Rabat Plan of Action has six elements: context, position and status of the speaker, intention, content and form of speech, range, and possibility and potential for harm. In this article, Rabat Plan of Action was applied to the case of Bambang Tri Mulyono, who believed that President Joko Widodo's diploma was fake and his speech had been uploaded on a YouTube video. The simulation results confirm that the Rabat Plan of Action can effectively provide directions for extracting legal facts and related events so that law enforcement officials can find clues in determining the occurrence of hate speech. Based on these results, the Rabat Plan of Action should be adopted at the national level to complement the legal instruments for handling acts of hate speech.